Divine gender transformations in Rebbe Nahman of Bratslav - Lewis, Justin (Nordisk judaistik/Scandinavian Jewish Studies, 2008)
In several passages in the tales and teachings of Rebbe Nahman of Bratslav, the divine undergoes a process of gender transformation. “The holy one blessed be he”, becomes female, and the Shekhinah temporarily takes on a male persona. Characterizations of Hasidic thought as androcentric generally apply to R’ Nahman. There is an accepted hierarchy and polarization of gender which informs much of his oeuvre. This article argues, however, that in these particular passages R’ Nahman disrupts this hierarchy. Whereas Kabbalah and Hasidism normally view the feminine as an outer “garment” for the divine masculine, in these passages the devotee discovers the hidden inwardness of God, which turns out to be feminine. This radical imagery is nourishing for followers of R’ Nahman’s controversial brand of Hasidism. In particular, it provides a theological justification for their unexpectedly intimate encounters with the divine, as they engage in the meditative practice of personal, solitary prayer according to R’ Nahman’s directives.